Semiotics of audit quality: a meta-analysis perspective - Saifudin Saifudin; Indira Januarti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: The purpose of this study is to identify the semiotics of the relationship between audit fees and audit quality.Design/Methodology/Approach: A quantitative method using meta-data analysis was employed with ten selected research articles from 113 sample articles.Research findings: The results demonstrated that a semiotic analysis of audit quality with a meta-analysis approach has been carried out, revealing that the audit fee variable had a relationship with audit quality and was strengthened by the size variable. The existing data heterogeneity problem was reduced after the size variable was included in the meta-analysis regression analysis, so it was reduced even though it had not been significantly reduced.Theoretical contribution/Originality: The semiotics of the relationship between audit fees and audit quality exist.Practitioner/Policy implication: This study contributes to paying attention to critical factors in improving audit quality.Research limitation/Implication: This study's limitations are that it could not reach the 95% data confidence coefficient level since the data used were still not much, and the size variable could not reduce data heterogeneity to the maximum.